Influence of biological sex and exercise on murine cardiac metabolism - Kyle Fulghum; Helen E. Collins; Steven P. Jones; Bradford G. Hill (Elsevier, 2022)
Although the structural and functional effects of exercise on the heart are well established, the metabolic changes that occur in the heart during and after exercise remain unclear. In this study, we used metabolomics to assess time-dependent changes in the murine cardiac metabolome following 1 session of treadmill exercise. After the exercise bout, we also recorded blood lactate, glucose, and ketone body levels and measured cardiac mitochondrial respiration. In both male and female mice, moderate- and high-intensity exercise acutely increased blood lactate levels. In both sexes, low- and moderate-intensity exercise augmented circulating 3-hydroxybutryrate levels immediately after the exercise bout; however, only in female mice did high-intensity exercise increase 3-hydroxybutyrate levels, with significant increases occurring 1 h after the exercise session. Untargeted metabolomics analyses of sedentary female and male hearts suggest considerable sex-dependent differences in basal cardiac metabolite levels, with female hearts characterized by higher levels of pantothenate, pyridoxamine, homoarginine, tryptophan, and several glycerophospholipid and sphingomyelin species and lower levels of numerous metabolites, including acetyl coenzyme A, glucuronate, gulonate, hydroxyproline, prolyl-hydroxyproline, carnosine, anserine, and carnitinylated and glycinated species, as compared with male hearts. Immediately after a bout of treadmill exercise, both male and female hearts had higher levels of corticosterone; however, female mice showed more extensive exercise-induced changes in the cardiac metabolome, characterized by significant, time-dependent changes in amino acids (e.g., serine, alanine, tyrosine, tryptophan, branched-chain amino acids) and the ketone body 3-hydroxybutyrate. Results from experiments using isolated cardiac mitochondria suggest that high-intensity treadmill exercise does not acutely affect respiration or mitochondrial coupling; however, female cardiac mitochondria demonstrate generally higher adenosine diphosphate sensitivity compared with male cardiac mitochondria. Collectively, these findings in mice reveal key sex-dependent differences in cardiac metabolism and suggest that the metabolic network in the female heart is more responsive to physiological stress caused by exercise.